THE PREPARA TION AND ECONOMIC VALUE OF INDIGENOUS MUKUMBI DRINK: AN AFRO-SENSED REFLECTION - Shokane, Allucia L; Badetswana, R; Mogorosi, Lobelo D (Southern African Journal for Folklore Studies, 2016)
For millennia, indigenous plants have been playing an essential role in the lives of indigenous people by satisfying their spiritual and material needs. This is also the case in rural areas, where indigenous plants contribute significantly as sources of shelter, clothing, firewood, medicine and food for local communities. This paper describes the process of innovation and the economic value of the indigenous marula drink, also referred to by the Tshivenda name, mukumbi. The article aims to focus on the nature of innovation and economic value of the mukumbi and also the article discusses its importance for socialisation. There are evident opportunities for the use of mukumbi. It therefore behoves one to seriously look the indigenous context where mukumbi is prepared and consumed. The central idea of the article is to advance and situate the course of indigenous knowledge scholarship by looking at mukumbi.